Exclusion of a Direct Progenitor Detection for the Type Ic SN 2017ein Based on Late-time Observations - Yi-Han Zhao; Ning-Chen Sun; Junjie Wu; Zexi Niu; Xinyi Hong; Yinhan Huang; Justyn R. Maund; Qiang Xi; Danfeng Xiang; Jifeng Liu (The Astrophysical Journal Letters, 2025)
To date, SN 2017ein is the only Type Ic supernova with a directly identified progenitor candidate. This candidate points to a very massive (>45 M _⊙ ) Wolf–Rayet (WR) progenitor, but its disappearance after the explosion of SN 2017ein remains unconfirmed. In this work, we revisit SN 2017ein in late-time images acquired by the Hubble Space Telescope at 2.4–3.8 yr after peak brightness. We find this source has not disappeared, and its brightness and color remain almost the same as in the preexplosion images. Thus, we conclude that the preexplosion source is not the genuine progenitor of SN 2017ein. It is not much likelier to be a companion star of the progenitor since it has a much lower extinction than SN 2017ein; its color also seems inconsistent with a star cluster, indicated by the newly added magnitude limit in F336W, apart from F555W and F814W. We suggest, therefore, this source is an unrelated star in chance alignment with SN 2017ein. Based on the low ejecta mass, we propose that SN 2017ein is most likely originated from a moderately massive star with M _ini  ∼ 8–20 M _⊙ , stripped by binary interaction, rather than a very massive WR progenitor.